Work stress in nurses returning to tertiary a general hospitals in China after the delivery of their second child: a cross-sectional study - Kai Chen; Lili Wei; Yan Zhang; Wenbin Jiang; Jingyuan Wang; Yueshuai Pan (BMC, 2022)
Abstract Objective To investigate the current situation of work stress in nurses returning to work in Chinese tertiary A general hospitals after giving birth to their second child and to analyze influencing factors. Methods From January to April 2021, 448 nurses returning to work after the birth of their second child, working in 23 general hospitals in China, were investigated and completed the postpartum work stress scale and self-rating depression scale. Results The total work stress score of returning nurses after giving birth to their second child was 90.40 ± 18.29, and the dimension with the highest score was the role commitment of the mother. Multiple linear regression analysis showed that family monthly income, turnover intention, time since returning to work, age of the first child, and depressive symptoms were the influencing factors on work stress. Conclusion It is important to reduce the work stress of the nurses returning to work after the birth of their second child. Nursing managers should pay attention to this group of postpartum nurses and formulate targeted measures to alleviate their work stress.